The Sharing Economy and Its Impact on The Local Economy - Rosalia, Olyvia; Heliyani; Firayani (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the impact of community participation in the sharing economy on local economic growth. The sharing economy, characterized by the rapid rise of digital platforms such as Gojek, Grab, Airbnb, and various other app-based services, has transformed the traditional economic landscape into a more collaborative and access-based system. This research adopts a quantitative approach with an associative method, involving 100 respondents who are users and providers of sharing economy services. Data were collected through closed-ended questionnaires and analyzed using simple linear regression to examine the relationship between the level of participation and indicators of local economic growth, such as increased income, job creation, and the involvement of MSMEs in the digital economy. The results show that participation in the sharing economy has a positive and significant impact on the local economy. In addition to being a source of supplementary income, the sharing economy also helps expand informal job opportunities and supports the digital transformation of small businesses. These findings provide a critical foundation for more inclusive and adaptive policymaking in response to digital economic developments and to promote community economic empowerment through technology adoption.